Cephalometric Floating Norms of Nepalese Adults Visiting People’s Dental College and Hospital with Harmonious Skeletal Pattern - Shrestha , Natasha; Sharma, Shakti; Roy, Prabhas; Kunwar, Prajwol Singh (International Journal of Silkroad Institute of Research and Training, 2024)
Background:Orthodontics blends art and science, with facial aesthetics reflecting orthodontists' creative insights, making proper diagnosis and treatment planning crucial for successful outcomes. This study aims to establish cephalometric floating norms for Nepalese adult patients. Method: A cross-sectional study was conducted among adult patients visiting People’s Dental College and Hospital from August 2018 to August 2019. The lateral cephalograms were selected based on inclusion and exclusion criteria. Pearson correlation coefficient was used to identify the highly correlated variables among the five parameters (SNA, SNB, NSBa, ML-NSL and NL-NSL). The bivariate linear regression analysis was used to construct a harmony box, which contained the cephalometric floating norms of the five correlated variables. Multiple regression analysis and the standard error of the estimate were calculated to construct the harmony schema, which describes the individual craniofacial pattern. Mean values of the continuous variables were compared (skeletal parameters) between gender, age group and ethnicity using independent sample t-test. Result: This study included 144 lateral cephalometric records, with 74% females. Statistically significant correlations were found among the five variables (SNA, SNB, NSBa, ML-NSL, NL-NSL), with SNB showing the highest correlation and used as the main variable for the regression equation. Significant gender differences were noted for NL-NSL (p < 0.05), but no significant differences were found among different ethnic and age groups. The harmony box illustrated linear regression equations, while the harmony schema was developed from standard errors and means of cephalometric measurements. Comparing Filipino and Nepalese adults showed Filipinos with a retrognathic maxilla and prognathic mandible, while Czech adults showed a retrognathic maxilla compared to Nepalese adults. Conclusion: Cephalometric floating norms describing the individual craniofacial pattern among Nepalese adults were established based on five correlated variables in the form of a harmony box.